Livestock producers' knowledge, attitude, and behavior (KAB) regarding antimicrobial use in Ethiopia - Tufa, Takele B.; Regassa, Fikru; Amenu, Kebede; Stegeman, J. A.; Hogeveen, Henk (Frontiers in Veterinary Science, 2023)
Inappropriate antimicrobials use (AMU) in livestock production is an important aspect of the global burden of antimicrobial resistance (AMR). In Ethiopia, a low-income country with a large and increasing livestock population, AMU in food animals is not properly regulated. Hence, farmers are fully free to use antimicrobials to their (perceived) benefit. Therefore, understanding farmers’ mindsets are important to improve antimicrobial stewardship in the livestock sector. This cross-sectional study was conducted to assess livestock disease management practices and knowledge, attitude, and behavior (KAB) amongst livestock producers regarding AMU, residues, and resistance as well as factors potentially explaining differences in KAB. We determined the KAB of livestock owners of three selected districts of central and western Ethiopia (n = 457) using a pretested questionnaire administered through face-to-face interviews. Logistic regression was used to evaluate the association between potential explanatory variables and the KAB scores of the respondents. The results showed that 44% of the farmers used antimicrobials in the past year, where antibiotics (21%) and trypanocides (11%) were most widely used to manage livestock diseases. Furthermore, most farmers showed poor knowledge about AMU, residues, and AMR (94%) and unfavorable attitudes (< 50% correct answers) toward contributing factors for AMR (97%). On the other hand, 80% of the respondents had good overall behavior scores ( ≥ 50% correct answers) related to AMU. Multivariate analysis results showed that having good knowledge, keeping ≥ 2 animal species and the occurrence of ≥ 4 livestock diseases on the farm in a year were strong predictors of bad behavior scores (p < 0.05). The findings of the current investigation also revealed that the incidence of livestock diseases on the farm and a higher level of formal education significantly contributed to better knowledge and desirable attitudes but bad AMU behavior. A low level of awareness about, and undesirable attitudes towards AMU and AMR could potentially affect farmers’ behavior towards judicious AMU, thus requiring awareness creation efforts on livestock disease management practices.